The crisis of school violence : a new perspective - King, Marianna (Michigan State University Press, 2021)
"The book investigates human nature and its relation to aggressive behavior. It describes the culture of violence that generates a culture of school violence, taking into account psychological and neuroscientific research exploring the effects of violent entertainment media on the brain and on behavior"--